Criteria for implementing interventions to reduce health inequalities in primary care settings in European regions. (16th April 2014) - Daponte, Antonio; Bernal, Mariola; Bolívar, Julia; Mateo, Inmaculada; Salmi, Louis-Rachid; Barsanti, Sara; Berghmans, Luc; Piznal, Ewelina; Bourgueil, Yann; Marquez, Soledad; González, Ingrid; Carriazo, Ana; et al.
Abstract : Background : The current social and political context is generating socio-economic inequalities between and within countries, causing and widening health inequalities. The development and implementation of interventions in primary health care (PHC) settings seem unavoidable. Attempts have been made to draw up adequate criteria to guide and evaluate interventions but none for the specific case of PHC. This methodological article aims to contribute to this field by developing and testing a set of criteria for guiding and evaluating real-life interventions to reduce health inequalities in PHC settings in European regions. Methods : A literature review, nominal group technique, survey and evaluation template were used to design and test a set of criteria. The questionnaire was answered by professionals in charge of 46 interventions carried out in 12 European countries, and collected detailed information about each intervention. Third-party experts scored the interventions using the set of evaluation criteria proposed. Results : Nine criteria to guide and evaluate interventions were proposed: relevance, appropriateness, applicability, innovation, quality assurance, adequacy of resources, effectiveness in the process, effectiveness in results and mainstreaming. A working definition was drawn up for each one. These criteria were then used to evaluate the interventions identified. Conclusions : The set of criteria drawn up to guide the design, implementation and evaluation of interventions to reduce health inequalities in PHC will be a useful instrument to be applied to interventions under development for culturally, politically and socio-economically diverse PHC contexts throughout Europe.